The level of mRNA encoding the amphotropic retrovirus receptor in mouse and human hematopoietic stem cells is low and correlates with the efficiency of retrovirus transduction. - Orlic, D (1996)
The low level of amphotropic retrovirus-mediated gene transfer into human hematopoietic stem cells (HSC) has been a major impediment to gene therapy for hematopoietic diseases. In the present study, we have examined amphotropic retrovirus receptor (amphoR) and ecotropic retrovirus receptor mRNA expression in highly purified populations of mouse and human HSC. Murine HSC with low to undetectable levels of amphoR mRNA and relatively high levels of ecotropic retrovirus receptor mRNA were studied. When these HSC were analyzed simultaneously for ecotropic and amphotropic retrovirus transduction, ecotropic provirus sequences were detected in 10 of 13 long-term repopulated animals, while amphotropic proviral sequences were detected in only one recipient. A second distinct population of murine HSC were isolated that express 3-fold higher levels of amphoR mRNA. When these HSC were analyzed simultaneously for ecotropic and amphotropic retrovirus transduction, 11 of 11 repopulated mice contained ecotropic provirus and 6 of 11 contained amphotropic provirus sequences, a significant increase in the amphotropic retrovirus transduction (P = 0.018). These results indicate that, among the heterogeneous populations of HSC present in adult mouse bone marrow, the subpopulation with the highest level of amphoR mRNA is more efficiently transduced by amphotropic retrovirus. In a related study, we found low levels of human amphoR mRNA in purified populations of human HSC (CD34+ CD38-) and higher levels in committed progenitor cells (CD34+ CD38+). We conclude that the amphoR mRNA level in HSC correlates with amphotropic retrovirus transduction efficiency.